2006
DOI: 10.1091/mbc.e05-08-0766
|View full text |Cite
|
Sign up to set email alerts
|

Shiga Toxin Regulates Its Entry in a Syk-dependent Manner

Abstract: Shiga toxin (Stx) is composed of an A-moiety that inhibits protein synthesis after translocation into the cytosol, and a B-moiety that binds to Gb3 at the cell surface and mediates endocytosis of the toxin. After endocytosis, Stx is transported retrogradely to the endoplasmic reticulum, and then the A-fragment enters the cytosol. In this study, we have investigated whether toxin-induced signaling is involved in its entry. Stx was found to activate Syk and induce rapid tyrosine phosphorylation of several protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 57 publications
5
90
0
Order By: Relevance
“…However, at 16 u C, protein synthesis inhibition remained steady at~50 % from 3 to 6 h of VT1 treatment and was not augmented by lactacystin proteosomal inhibition. This protein synthesis inhibition could result from signal transduction involving VTA or VT1 holotoxin, rather than from cytosolic translocation (Katagiri et al, 1999;Lauvrak et al, 2006;Mori et al, 2000), as VTB alone was incapable of reducing protein synthesis at 16 u C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at 16 u C, protein synthesis inhibition remained steady at~50 % from 3 to 6 h of VT1 treatment and was not augmented by lactacystin proteosomal inhibition. This protein synthesis inhibition could result from signal transduction involving VTA or VT1 holotoxin, rather than from cytosolic translocation (Katagiri et al, 1999;Lauvrak et al, 2006;Mori et al, 2000), as VTB alone was incapable of reducing protein synthesis at 16 u C.…”
Section: Discussionmentioning
confidence: 99%
“…The VT1-Gb 3 complex is internalized by receptor-mediated endocytosis (Khine & Lingwood, 1994;Sandvig et al, 1989), both clathrin and caveolae dependent (Nichols et al, 2001). Following kinase-dependent endocytosis (Lauvrak et al, 2006), VT1 exploits a retrograde transport route to the Golgi and endoplasmic reticulum (ER) (Sandvig et al, 1992). This Golgi/ER retrograde transport pathway has been characterized using VTB (Johannes et al, 1997), and sorting along this pathway is also clathrin dependent (Lauvrak et al, 2004;Saint-Pol et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is well documented that tyrosine-and ser/thr kinases are activated, and phosphatase inhibitors elevate vesicle formation (Richards et al 2002). In the case of STX and CTX, binding to the plasma membrane can activate Src-family kinases (SFKs) that copurify in detergent resistant membrane fractions (Katagiri et al 1999) and regulate endocytosis (Lauvrak et al 2006). …”
Section: Lipid-mediated Endocytosismentioning
confidence: 99%
“…Interestingly, it has been shown that Stx binding rapidly activates several kinases, such as the Src kinases Yes [28,29] and Lyn [30], the tyrosine kinase Syk [30,31], the serine/threonine kinase PKC [32], and the MAP kinase p38 [33]. The activity of some of these kinases is important for Stx entry and intracellular transport, suggesting that Stx is able to induce its own transport (see below).…”
Section: Binding Of Stx To Cellular Membranesmentioning
confidence: 99%
“…clathrin and uptake by this pathway [31], however, the efficiency of clathrin-mediated toxin uptake is dependent on the concentration of cell surface-bound toxin molecules and the presence of the toxin A-chain [35]. The stimulated uptake seen at high concentrations of intact toxin, might be explained by increased aggregation of toxin-receptorcomplexes into large clusters that somehow enhance the recruitment to clathrin-coated pits.…”
Section: B B Bmentioning
confidence: 99%